2022
DOI: 10.52711/2454-2652.2022.00071
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of mothers regarding developmental milestones of infants: A Descriptive Cross-sectional study

Abstract: Developmental milestones in children or infants are a certain set of skills or age-specific tasks. Missed or delayed milestones in infancy can be symptoms of serious medical conditions. If parents understand their children’s development, they can tailor their expectations and provide stimulation. This study was conducted to assess the level of knowledge regarding the development milestones of infants among mothers. A descriptive study was conducted on 100 mothers of neonates visiting pediatric OPD and gynecolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…Women were working as unskilled workers to do minor manual operations on manufactured hosiery garments like stitching, embroidering and finishing etc. Kaur and Kaur, 2004 also reported that in Ludhiana hosiery industry, majority of the workers were hired on daily wages or piece rate system. According to Titi, (2019) size of an industry is determined on the basis of number of employees and output levels.…”
Section: Employment Patternmentioning
confidence: 98%
“…Women were working as unskilled workers to do minor manual operations on manufactured hosiery garments like stitching, embroidering and finishing etc. Kaur and Kaur, 2004 also reported that in Ludhiana hosiery industry, majority of the workers were hired on daily wages or piece rate system. According to Titi, (2019) size of an industry is determined on the basis of number of employees and output levels.…”
Section: Employment Patternmentioning
confidence: 98%
“…Indirect (secondary) benefits related to process improvements, such as optimization, pragmatic decision-making, better process management, and alternative methods. RM is to prevent and control risks before they get worse, so, risk monitoring and maintenance steps are adopted in the RM plan [29] SRM involves thoroughly ing the system or process to identify problems or potential risks, analyze them, and develop strategies to mitigate and control risks. Mitigating software risks does not mean immediately eliminating all risks that caused the failure.…”
Section: Software Risk Management (Srm)mentioning
confidence: 99%
“…As [29] distinguished, software risks are mainly divided into three categories: technical risk, schedule/scope, and cost. Technical risks are associated with the performance of software products, including functional, quality, reliability, and timeliness issues [29].…”
Section: Software Risk Categoriesmentioning
confidence: 99%
See 2 more Smart Citations